High‐energy radiation belt electrons from CRAND. Issue 4 (30th April 2015) - Selesnick, R. S.
Abstract A calculation of the inner radiation belt electron source from cosmic ray albedo neutron decay (CRAND) is described. High‐energy electrons are included by Lorentz‐transforming the β decay spectrum from the neutron rest frame to the Earth's rest frame and combining with the known high‐energy albedo neutron energy spectrum. Balancing the electron source with energy loss to atmospheric neutral atoms and plasma, and with a decay lifetime representative of plasma wave scattering, then provides an estimate of trapped electron intensity. It is well below measured values for low energies, confirming that CRAND is not a significant source of those trapped electrons. For kinetic energies above the maximum β decay energy (E > 0.8 MeV) a power law energy spectrum ∼E−4 is predicted. For L = 1.5 and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjng79t5k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />E≳2</alternatives> MeV the computed omnidirectional trapped electron intensity exceeds an extrapolation of the measured low‐energy exponential energy spectrum.